Environmental impact assessment using a weighted global index: A methodological proposal - Ribeiro, Admilson Írio [UNESP]; Bressane, Adriano; Fengler, Felipe Hashimoto [UNESP]; Longo, Regina Marcia; Da Silva, Alessandra Leite; Roveda, Jose Arnaldo F. [UNESP]; Ribeiro, Marcus Vinicius; De Medeiros, Gerson Araujo [UNESP] (WITPRESS LTD., 2018)
Activities considered effectively or potentially polluting depend on an environmental impact assessment before starting their installation and operations. However, the lack of a structured logical procedure for supporting decision-making may compromise the comparative analysis of alternatives available. In this paper we present a methodological proposal based on a weighted global index (igiw) for comparative analysis in environmental impact assessments. For that, the impact global index (igi), originally developed by Bressane et al., was improved taking into account an additional weighting based on the prioritization of impacts according to their relative importance case-by-case. Then, the new index was used on two case studies. In the first one, the igiw was applied to support decisionmaking on maintenance or demolishing of the buildings in situation of irregularity. Secondly, several technologies and siting alternatives have been compared for installing a sewage treatment plant into an urban condominium. As a result, it was found that the weighted impact global index was able to critically and comprehensively evaluate the alternatives available for both cases under study. In conclusion the igiw may be considered a promising approach as a method for supporting decisionmaking in environmental impact assessments.
Keywords: Environmental assessment; Global index; Project alternatives